Immunological and Molecular Method for the Diagnosis of Human Bocavirus in Patients with Respiratory Infections in Mosul, Iraq - Anmar A. AlTaie; Noor Raad Abdulghany; Muhammad Abdul-Ghani Muhammad; Mohammad M. Salih; Iman Mutasher Aufi (Medical Journal of Babylon)
Background: Human bocavirus (HBoV) typically affects adolescents and causes upper and lower respiratory infections. However, little is known about the clinical features of this pathogen and its implications for respiratory infections in adults. Objectives: To detect the HBoV effect on adults and adolescents causing respiratory diseases in the lower respiratory tract. Materials and Methods: Seventy throat and nasopharyngeal swabs were collected from male and female patients, aged 11–57 years, from three hospitals in Mosul City, Iraq, within 6 months in 2024. The samples were stored in a viral transport medium until indirect enzyme-linked immunosorbent assay and real-time polymerase chain reaction (RT-PCR) were performed. Results: Out of 70 samples, the prevalence rate of immunoglobulin (Ig)M antibodies was 37 (53%), IgG was 33 (47%), and viral DNA for HBoV was 24 (34%), respectively. The dominating age groups were above 30 years, and males were more susceptible to infection compared with females. Conclusion: The best diagnostic method for the detection of HBoV is RT-PCR. The present study highlights RT-PCR in diagnosing respiratory infections. This technique can be compared with other immunological methods to determine the severity of the disease.